The science of meat quality - Kerth, Chris R. (Oxford : Wiley-Blackwell, 2013)
'The Science of Meat Quality looks at the development of quality meat products from the physiological processes that result in meat development through to final consumption of meat products. Each chapter opens with theoretical foundations to meat science practices alongside methodologies for measuring quality in relation specific aspects of meat and also provides the necessary tools to interpreting information gleaned from quality experimentation. The Science of Meat Quality will be an essential purchase for all animal and meat scientists concerned with the production of quality meat products'--
'This book provides an in-depth study of the development of quality meat products, from the physiological processes that result in meat development through to final consumption of meat products. Each chapter opens with theoretical foundations to meat science practices alongside methodologies for measuring quality in relation to specific aspects of meat. Providing the necessary tools to interpret information gleaned from quality experimentation, this book is an essential purchase for all animal and meat scientists concerned with the production of quality meat products'--
Growth of Muscle from the Myoblast to Whole Muscle / Terry Brandebourg -- Animal Growth and Empty Body Composition / Michael Dikeman -- Muscle Structure and Cytoskeletal Proteins / Chris R Kerth -- Muscle Metabolism and Contraction / Chris R Kerth -- Converting Muscle to Meat: The Physiology of Rigor / Kirk W Braden -- Meat Tenderness / Chris R Kerth -- Water-Holding Capacity of Meat / Jason K Apple, Janeal WS Yancey -- Lipids and Lipid Oxidation / Kyle Willian -- Meat Color / Richard Mancini -- Meat Cookery / Clinton Rowe, Chris R Kerth -- Trained Sensory Panels / Christy L Bratcher -- Untrained Sensory Panels / Patricia C Curtis -- Consumer Sensory Panels / Ryan Cox -- Preventing Foodborne Illness / Michael A Davis.
Includes bibliographical references and index.
Online resource; title from home title page (Wiley; viewed on May 13, 2012).
Keywords: Meat -- Quality; Meat industry and trade -- Quality control; Electronic books